2019
DOI: 10.5694/mja2.50394
|View full text |Cite
|
Sign up to set email alerts
|

Routine glucose assessment in the emergency department for detecting unrecognised diabetes: a cluster randomised trial

Abstract: Objective To determine whether routine blood glucose assessment of patients admitted to hospital from emergency departments (EDs) results in higher rates of new diagnoses of diabetes and documentation of follow‐up plans. Design, setting Cluster randomised trial in 18 New South Wales public district and tertiary hospitals, 31 May 2011 – 31 December 2012; outcomes follow‐up to 31 March 2016. Participants Patients aged 18 years or more admitted to hospital from EDs. Intervention Routine blood glucose assessment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Patients frequently misused pregabalin together with other sedatives, particularly benzodiazepines, and almost 40% of misuse‐related events requiring paramedic attendance were suicide attempts. Caution is required when prescribing pregabalin, especially for patients using other sedatives. In a cluster randomised controlled trial in 18 NSW hospitals, Cheung and his colleagues examined whether screening emergency department patients improves the detection of unrecognised diabetes. The investigators found that automatically requesting HbA 1c assessments of patients with blood glucose levels of 14 mmol/L or more and notifying hospital diabetes services were insufficient for improving care, and needed to be supported by more comprehensive, systems‐based solutions. In an open label randomised controlled trial in a tertiary maternity hospital, White and his co‐authors found that circulating Rh(D)‐immunoglobulin (anti‐D) was detectable at delivery in a greater proportion of Rh(D)‐negative women who had received antenatal anti‐D prophylaxis as two doses (at 28–30 and 34–36 weeks of pregnancy: 111 of 129, 86%) than of women who received it as a single dose (28–30 weeks: 70 of 125, 56%).…”
Section: Articles Short‐listed For the Mja Mda National Prize For Exmentioning
confidence: 99%
“…Patients frequently misused pregabalin together with other sedatives, particularly benzodiazepines, and almost 40% of misuse‐related events requiring paramedic attendance were suicide attempts. Caution is required when prescribing pregabalin, especially for patients using other sedatives. In a cluster randomised controlled trial in 18 NSW hospitals, Cheung and his colleagues examined whether screening emergency department patients improves the detection of unrecognised diabetes. The investigators found that automatically requesting HbA 1c assessments of patients with blood glucose levels of 14 mmol/L or more and notifying hospital diabetes services were insufficient for improving care, and needed to be supported by more comprehensive, systems‐based solutions. In an open label randomised controlled trial in a tertiary maternity hospital, White and his co‐authors found that circulating Rh(D)‐immunoglobulin (anti‐D) was detectable at delivery in a greater proportion of Rh(D)‐negative women who had received antenatal anti‐D prophylaxis as two doses (at 28–30 and 34–36 weeks of pregnancy: 111 of 129, 86%) than of women who received it as a single dose (28–30 weeks: 70 of 125, 56%).…”
Section: Articles Short‐listed For the Mja Mda National Prize For Exmentioning
confidence: 99%
“…The rationale for the decision to use >14 mmol/L as a cut‐off in this study was the risk of overburdening the clinicians if a lower value was used 2 . The authors report that automatically triggering HbA1c measurements in their intervention group did not lead to increased rates of diabetes diagnoses in hospital 6 . Another Australian study used a cut‐off of 5.5 mmol/L among people presenting to the emergency department to trigger HbA1c measurement 3 .…”
Section: Introductionmentioning
confidence: 98%
“…For example, one study examined the use of automatically triggered HbA1c measurements for 133,837 people admitted to secondary and tertiary hospitals in New South Wales, Australia, during 2011 and 2012. The study used a plasma glucose value of >14 mmol/L as the cut‐off 6 . The authors cite “stress hyperglycaemia” as the main differential diagnosis in the inpatient with hyperglycaemia.…”
Section: Introductionmentioning
confidence: 99%
“…A trial by Cheung et al of routine glucose assessment in the emergency department found that automatic requests for HbA1c assessment significantly increased HbA1c testing, but this passive process did not translate to greater diabetes diagnosis or documentation of follow-up plans. 3 However, management interventions that have included proactive involvement of the specialist team have shown increased glucose-lowering therapy prescription and improved glucose. 4 Furthermore, a sustained proactive intervention appears to be required to achieve sustained improvements in clinical care.…”
mentioning
confidence: 99%